Chronic obstructive pulmonary disease: risk factors, exacerbations and therapeutic implications. - Vytor Cardoso Nobre, Paulo (2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a worldwide condition characterized by the persistent presence of chronic inflammation of the airways, resulting in a progressive restriction of airflow. Objective: To evaluate the risk factors, exacerbations and therapeutic aspects of chronic obstructive pulmonary disease. Methodology: This is a bibliographic review that included original articles and systematic reviews in English and Portuguese, which addressed risk factors for exacerbations and management of COPD, published between 2015 and 2024, selected from the PubMed, Scopus and SciELO databases. After careful selection, 20 articles were chosen to compose this bibliographic review. Results: There are several risk factors that contribute to the condition, such as bacterial and viral infections, smoking, air pollution and exposure to residential biomass. Management includes pharmacological and non-pharmacological interventions, with an emphasis on smoking cessation as a central priority. The pharmacological approach includes beta-2 agonists, antimuscarinics and corticosteroids. Considerations: Managing COPD requires a broad understanding of the risk factors that exacerbate the clinical state and contribute to recurrent hospitalizations. Management strategies, including pharmacological and non-pharmacological interventions, with an emphasis on smoking cessation, are essential. Pharmacological treatment has been shown to be effective, especially triple therapy, and is crucial for reducing exacerbations and improving the quality of life of patients with COPD.